High-resolution manometry: Reliability of automated analysis of upper esophageal sphincter relaxation parameters - Lee, Tae Hee; Lee, Joon Seong; Hong, Su Jin; Lee, Ji Sung; Jeon, Seong Ran; Kim, Wan Jung; Kim, Hyun Gun; Cho, Joo Young; Kim, Jin-Oh; Cho, Jun-Hyung; Park, Won Young; Park, Ji Woong; et al. (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: At present, automated analysis of high-resolution manometry (HRM) provides details of upper esophageal sphincter (UES) relaxation parameters. The aim of this study was to assess the accuracy of automatic analysis of UES relaxation parameters. Materials and Methods: One hundred and fifty three subjects (78 males, mean age 68.6 years, range 26-97) underwent HRM. UES relaxation parameters were interpreted twice, once visually (V) by two experts and once automatically (AS) using the ManoView ESO analysis software. Agreement between the two analysis methods was assessed using Bland-Altman plots and Lin’s concordance correlation coefficient (CCC). Results: The agreement between V and AS analyses of basal UES pressure (CCC 0.996; 95% confidence interval (CI) 0.994-0.997) and residual UES pressure (CCC 0.918; 95% CI 0.895-0.936) was good to excellent. Agreement for time to UES relaxation nadir (CCC 0.208; 95% CI 0.068-0.339) and UES relaxation duration (CCC 0.286; 95% CI 0.148-0.413) between V and AS analyses was poor. There was moderate agreement for recovery time of UES relaxation (CCC 0.522; 95% CI 0.397-0.627) and peak pharyngeal pressure (CCC 0.695; 95% CI 0.605-0.767) between V and AS analysis. Conclusion: AS analysis was unreliable, especially regarding the time variables of UES relaxation. Due to the difference in the clinical interpretation of pharyngoesophageal dysfunction between V and AS analysis, the use of visual analysis is justified.